The Icarus Line must die [videorecording (Blu-Ray)] - Cardamone, Charlotte; Cardamone, Joe; Charles, Pearl; Morris, Keith (Vocalist) (Darkstar Pictures, 2022)
A dramatic narrative feature set against the backdrop of the current LA underground music scene. The film tracks Joe Cardamone, front man of notorious punk bad boys The Icarus Line as he navigates his way through the ups and downs of the modern music landscape. With a new record completed and a major label deal within sight, Joe fights to keep his band, his relationship and his life from completely falling apart.